ANALISIS DAMPAK VARIABEL VARIABEL MARKETING MIX DALAM MEMBANGUN KEPUASAN PELANGGAN TOKO MEBEL DINA PARE KEDIRI (Studi Pada Pelanggan Toko Mebel Dina Pare Kediri) - Ike edwin stya wandira; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT Competition in today's business world is so tight that as the number of business people increases to meet consumer needs, both goods and services, businesses are increasingly facing challenges to get the market share they want. Meeting the needs and desires of consumers requires a marketing concept called the marketing mix where to apply a good marketing mix is to pay attention to the elements of supply, price, promotion and distribution of selling products. In marketing there is a marketing strategy called the marketing mix or marketing mix which has an important role in influencing consumers to be able to buy a product or service offered by the company. The mix used in this study are products, prices, places and promotions. This research was conducted at the Dina Pare Furniture Shop located on Wr. Supratman No.35 Pare Kediri. This research was conducted to find out the impact of 4p variables affecting customer satisfaction in the Furniture Shop. From this study it was found that the product mix marketing variable, price, place and promotion affect customer satisfaction. Furniture Dina has good quality products, has a good model, there are many variations and the design of the products sold in the Dina Furniture Shop is interesting. Prices of Furniture in Toko Dina are cheap The price of the product in the Dina Store competes with other stores. Shop Dina has a fixed discount. The shop has a discount every month. The price of products in Dina Stores is affordable. The advertisement owned by the Dina Shop is interesting. Ads owned by Dina Stores according to the product. Dina's store has a brochure ad. Attractive store promotions are attractive sales. Clean storefront The location of Toko Dina is easily accessible to customers. Toko Dina has an outdoor parking lot. Shops are driven by public transportation. Toko Dina is comfortable. And supported by Shop Customer results, Dina is happy, Dina's Shop Customers want to buy again. Customers are willing to buy products at Dina Stores. Customers are willing to recommend. Customers happy or satisfied. Products at Dina Shop are priced accordingly. Keywords: Marketing mix, customer satisfaction